Educação em ciências naturais para estudantes surdos : potencialidades e desafios no uso de uma plataforma virtual - Miranda, Joelson Marcelo de (2020)
The education of deaf people is today a big challenge for educators and managers of education systems. There is an understanding that it is necessary to overcome the barriers imposed by the historical process of exclusion of the deaf, which implies recognition that the deaf people make use of cultural artifacts that are their own, including the signal language. Consequently, the education of this social group needs to be promoted based on the assumptions of deaf pedagogy. Such assumptions are based on the fact that deaf individuals perceive the world through their eyes. This explains why the Digital Information and Communication Technologies (DICTs) are pointed out by deaf researchers as important pedagogical resources. This question was adopted as the object of this study, which is guided by the search for an answer to the next question (research problem): What potentialities can be observed when using the WIX Virtual Platform to promote education in natural sciences for deaf students of the last years of basic education? It is based on the understanding that the development of this study requires permanent dialogue with deaf teachers who work in a specialized school. For this reason, participant research was chosen as a methodological way. It is a research based on the collective construction of a WIX Virtual Platform dedicated especially to the production of didactic propositions of education in natural sciences for deaf students of the 3rd cycle of basic school. The theoretical support for the development of analyzes was found in cultural studies, more specifically, in the field of deaf studies. The research presented here is expected to support the school inclusion of deaf students, notably with regard to access to scientific culture.